Aristophanes and the poetics of surprise - Kanellakis, D (2019)
The purpose of this thesis is to examine the variety, the mechanisms, and the poetological intention of the effect of surprise in Aristophanic comedy, addressing the phenomenon not as a self-evident or unselfconscious element of comedy as a genre, but as an elaborate system which characterises the style of the specific dramatist. More precisely, the thesis analyses Aristophanes’ most prominent verbal, thematic, and theatrical modes of surprise from a typological perspective, and interprets them as comprising the key area in which the playwright claims and demonstrates his artistic superiority over rival genres and individual poets. In line with this purpose, two parallel aims of the thesis are to provide an original commentary on the passages under examination, and to promote the study of modern performances – a practice which has so far been either restricted to Classical Reception or only theoretically acknowledged (if at all) by mainstream philological scholarship.